Tetrapyrrolic Pigments from Heme‐ and Chlorophyll Breakdown are Actin‐Targeting Compounds. Issue 41 (31st August 2021) - Karg, Cornelia A.; Wang, Shuaijun; Al Danaf, Nader; Pemberton, Ryan P.; Bernard, Denzil; Kretschmer, Maibritt; Schneider, Sabine; Zisis, Themistoklis; Vollmar, Angelika M.; Lamb, Don C.; Zahler, Stefan; Moser, Simone
Abstract: Chlorophyll and heme are among the "pigments of life", tetrapyrrolic structures, without which life on Earth would not be possible. Their catabolites, the phyllobilins and the bilins, respectively, share not only structural features, but also a similar story: Long considered waste products of detoxification processes, important bioactivities for both classes have now been demonstrated. For phyllobilins, however, research on physiological roles is sparse. Here, we introduce actin, the major component of the cytoskeleton, as the first discovered target of phyllobilins and as a novel target of bilins. We demonstrate the inhibition of actin dynamics in vitro and effects on actin and related processes in cancer cells. A direct interaction with G‐actin is shown by in silico studies and confirmed by affinity chromatography. Our findings open a new chapter in bioactivities of tetrapyrroles—especially phyllobilins—for which they form the basis for broad implications in plant science, ecology, and physiology. Abstract : The physiological role of the degradation products of chlorophyll and heme, exogenous phyllobilins and endogenous bilins, respectively, remained an unsolved mystery for decades. We describe the influence of these tetrapyrroles on the actin cytoskeleton and introduce G‐actin as the first human target protein for phyllobilins and a novel target for bilins. This study opens up a new perspective of the importance of these ubiquitous natural products.